MEASURING THE CAPITAL STRUCTURE, PROFITABILITY AND EVA: WITH REFERENCE TO SELECTED AVIATION FIRMS IN INDIA - Angayarkanni, Dr R (IJRDO - Journal of Social Science and Humanities Research, 2018)
Capital structure decision is the vital one since the profitability of an enterprise is directly affected by such decision. The successful selection and use of capital is one of the key elements of the firms’ financial strategy. Hence, proper care and attention need to be given while determining capital structure decision. The purpose of this study is to investigate the relationship between capital structure and profitability of Company and to measure its impact on EVA. Design/methodology/approach: Different conditional theories of capital structure are reviewed (the trade‐off theory, pecking order theory, agency theory, and theory of free cash flow) in order to formulate testable propositions concerning the determinants of capital structure of select Indian Aviation firms. The investigation is performed using the secondary data collected from the reputed database for the purpose of analysis and interpretation. With regard to the sample size, we have taken top five Aviation firms from the Indian context. Findings: The results suggest that profitability, liquidity, earnings volatility, and tangibility (asset structure) are related negatively to the debt ratio, whereas firm size is positively linked to the debt ratio. Non‐debt tax shields and growth opportunities do not appear to be significantly related to the debt ratio. The data has been analysed by using descriptive statistics and Originality/value: To the authors’ knowledge, research ideas were the initial source for formulating this model. The authors have gone through various literature scrutinizations to past theories for identification of those variables which are more promising for the determination of capital structure.